Can Potassium Silicate Mineral Products Replace Conventional Potassium Fertilizers in Rice–Wheat Rotation?. (1st July 2019) - Zhao, Xinlin; Gao, Shuaishuai; Lu, Dianjun; Wang, Huoyan; Chen, Xiaoqin; Zhou, Jianmin; Zhang, Lei
Abstract : Core Ideas: We assessed the effects of several mineral fertilizers on crop yield and soil potassium fertility. The mineral fertilizers could maintain crop yield and soil potassium fertility. The mineral fertilizers could increase soil pH. The mineral fertilizers can partly replace conventional potassium fertilizers. Potassium (K) silicate minerals are important insoluble K resources and exploring their potential as alternatives to conventional K fertilizers would be helpful to deal with the widespread K deficiency in the world. Thus on‐farm experiments with potassium silicate mineral products (KSMPs), e.g., Fubang (FB), Zhongke (ZK), Ziguang (ZG)—manufactured from natural K‐bearing rocks—were conducted to investigate their effects on crop yield, soil K fertility and pH in rice‐wheat (Oryza sativa L.–Triticum aestivum L.) rotation at Guangde County and Jiangdu County, China. The experiments lasted 2 yr at two sites and six treatments about K fertilizers were tested: no K fertilization (CK); 100% K chloride (KCl); 100% ZG; 50% KCl +50% ZG; 50% KCl +50% FB; 50% KCl +50% ZK. Results showed that both wheat and rice grain yields for CK were markedly decreased compared with that for the other treatments, regardless of K fertilizer types. Similar to KCl, the KSMPs could maintain crop yields and soil potassium fertility. Besides, the KSMPs significantly improved soil pH by average 0.47 and 0.38 at Guangde and Jiangdu, respectively, compared with that for KCl, after its application for 2 yr. However, the apparent K balances for most treatments at two sites were negative. In terms of economic aspect, the value cost ratio averaged by sites of ZG was 2.59 which was significantly higher than that for FB and ZK. In conclusion, the KSMPs can sustain crop yields and soil K fertility and thus can partly substitute conventional K fertilizers in rice‐wheat rotation on the Aquic Haplanthrepts soils.